2007
DOI: 10.1074/jbc.m703771200
|View full text |Cite
|
Sign up to set email alerts
|

P-Rex1 Links Mammalian Target of Rapamycin Signaling to Rac Activation and Cell Migration

Abstract: Polarized cell migration results from the transduction of extracellular cues promoting the activation of Rho GTPases with the intervention of multidomain proteins, including guanine exchange factors. P-Rex1 and P-Rex2 are Rac GEFs connecting G␤␥ and phosphatidylinositol 3-kinase signaling to Rac activation. Their complex architecture suggests their regulation by protein-protein interactions. Novel mechanisms of activation of Rho GTPases are associated with mammalian target of rapamycin (mTOR), a serine/ threon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
166
1
1

Year Published

2008
2008
2012
2012

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 160 publications
(177 citation statements)
references
References 31 publications
7
166
1
1
Order By: Relevance
“…mTORC1 phosphorylates p70 S6 Kinase and eukaryotic initiation factor 4E binding protein 1 which activate translational machinery to increase cell proliferation [6,7]. mTORC2 is composed of mTOR binding to rapamycin insensitive companion of mTOR (Rictor), GβL, stress-activated protein kinase-interacting protein 1 (Sin1) and the newly discovered associations with PRoline-Rich protein 5 (PRR5) or the synonymous protein observed with Rictor 1 (Protor-1), and P-REX1 [8][9][10][11][12]. mTORC2 activates Akt at Ser473, Rac GTPase, cell migration and effects reorganization of the actin cytoskeleton [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…mTORC1 phosphorylates p70 S6 Kinase and eukaryotic initiation factor 4E binding protein 1 which activate translational machinery to increase cell proliferation [6,7]. mTORC2 is composed of mTOR binding to rapamycin insensitive companion of mTOR (Rictor), GβL, stress-activated protein kinase-interacting protein 1 (Sin1) and the newly discovered associations with PRoline-Rich protein 5 (PRR5) or the synonymous protein observed with Rictor 1 (Protor-1), and P-REX1 [8][9][10][11][12]. mTORC2 activates Akt at Ser473, Rac GTPase, cell migration and effects reorganization of the actin cytoskeleton [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…mTORC2 is composed of mTOR binding to rapamycin insensitive companion of mTOR (Rictor), GβL, stress-activated protein kinase-interacting protein 1 (Sin1) and the newly discovered associations with PRoline-Rich protein 5 (PRR5) or the synonymous protein observed with Rictor 1 (Protor-1), and P-REX1 [8][9][10][11][12]. mTORC2 activates Akt at Ser473, Rac GTPase, cell migration and effects reorganization of the actin cytoskeleton [11][12][13][14]. Recent work utilizing mouse knockout models emphasizes the importance of mTOR for growth and proliferation in development [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the Rac GEFs P-Rex 1 and 2 have been shown to associate with either mTORC1 or mTORC2 and participate in Rac-mediated migration of fibroblasts and tumorderived cell lines. 26 Short-term rapamycin treatment of particular tumor cell lines did not inhibit migration, indicating P-Rex association with the less sensitive mTORC2 complex is likely important for migratory responses. 26 However, the cell lines examined in this study have been previously shown to maintain mTORC2 activity after prolonged rapamycin treatment, 8 rendering them more rapamycinresistant than most T cell subsets.…”
Section: Regulation Of T Cell Migration and Morphology Change By Mtormentioning
confidence: 99%
“…26 Short-term rapamycin treatment of particular tumor cell lines did not inhibit migration, indicating P-Rex association with the less sensitive mTORC2 complex is likely important for migratory responses. 26 However, the cell lines examined in this study have been previously shown to maintain mTORC2 activity after prolonged rapamycin treatment, 8 rendering them more rapamycinresistant than most T cell subsets. It may be of interest to determine whether P-Rex 1 and 2 are expressed in T cells and whether they associate with mTORC1 or mTORC2 to regulate starvation-mediated migration.…”
Section: Regulation Of T Cell Migration and Morphology Change By Mtormentioning
confidence: 99%
“…132,133 mTORC2 directly interacted with and regulated Prex1, a Rac1 guanine nucleotide exchange factor that controls cytoskeletal rearrangement. 134 Although this discussion has been restricted to direct mTOR signaling interactions (Fig. 3), certain indirect effects of mTOR on biological processes relevant to LAM are worthy of mention.…”
Section: Other Emerging Mtor Targets In Lammentioning
confidence: 99%